Literasi Membaca dan Menulis untuk Meningkatkan Kualitas Mengajar Guru: Reading and Writing Literacy to Improve Teacher Teaching Quality - Ahmad Mubasir; EE Junaedi Sastradiharja; Farizal Farizal (ITScience (Information Technology and Science), 2025)
Reading and writing literacy is an important starting point for the educational process. Teachers must master the subject matter and have critical, creative, and communicative thinking skills to meet the demands of increasing educational standards. Through literacy, teachers can broaden their perspectives, gain a comprehensive understanding of the subject matter, and keep up with the latest developments in education and knowledge by developing their reading literacy. This study aims to analyze and describe the improvement of the quality of teacher teaching, namely the role of teacher reading and writing literacy in improving the quality of teaching at MTs Darunnajah Jakarta. This study uses qualitative data. Qualitative data are research findings not obtained from statistical analysis or other calculations. The data is only in the form of words. To improve the quality of teaching, teachers need to develop themselves by reading, taking training, and conducting research, based on Law Number 14 of 2005 concerning Teachers and Lecturers, which emphasizes professionalism through certification and four main competencies, namely pedagogical, professional, personality, and social, teachers must grow as individuals through reading, training, and research in order to improve the quality of their learning. The relationship between teachers and students also impacts the success of teaching; a friendly atmosphere and emotional support can increase student motivation and engagement in the classroom. Reading and writing literacy are essential to improving the quality of educators, especially during the teaching process. Teachers with good literacy skills can better understand and internalize subject matter, create reports and learning modules, and positively influence their students' learning outcomes. Through teacher monitoring, training, and research, principals can also help improve the quality of teacher learning.